2018
DOI: 10.1007/s00268-018-4504-2
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Trial of Use of In‐House Prepared Low‐Cost Radiopharmaceutical Versus Commercial Radiopharmaceutical for Sentinel Lymph Node Biopsy in Patients with Early Stage Invasive Breast Cancer

Abstract: In this prospective randomized trial on early breast cancer patients, accuracy of SLNB was comparable using in-house prepared, Tc-antimony colloid and commercially marketedTc-sulphur colloid as radiopharmaceutical, while Tc-antimony colloid was much cheaper thanTc-sulphur colloid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Meta-analyses and other studies have, however, refuted these findings, as MBD alone was found to have unacceptably high FNR [5,18]. We demonstrated that low-cost in-house-produced radioactive antimony colloid in combination with MBD was a cheaper and equally efficacious alternative to the commercially available radioactive Sulfur-colloid in a randomized study [17,25]. The radioactive antimony is a low-cost alternative in centers having nuclear medicine facilities.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Meta-analyses and other studies have, however, refuted these findings, as MBD alone was found to have unacceptably high FNR [5,18]. We demonstrated that low-cost in-house-produced radioactive antimony colloid in combination with MBD was a cheaper and equally efficacious alternative to the commercially available radioactive Sulfur-colloid in a randomized study [17,25]. The radioactive antimony is a low-cost alternative in centers having nuclear medicine facilities.…”
Section: Discussionmentioning
confidence: 79%
“…Exclusions were as follows: pregnancy, prior chemotherapy, surgery or radiation to, or scarring of breast or axilla, multiple tumors, allergy to any tracers, and refusal to undergo a validation axillary clearance. Patients were planned for either a breast conserving surgery or a mastectomy along with validation SLNB for axilla as previously described by us [16, 17]. In validation SLNB, we performed SLNB followed by removing “rest of axillary tissue.” Site of injection for all three dyes was half sub‐areolar and half peri‐tumoral in breast parenchyma.…”
Section: Methodsmentioning
confidence: 99%